Dynamic Silos: Modularity in intra-organizational communication networks before and during the Covid-19 pandemic - Zuzul, Tiona; Pahnke, Emily Cox; Larson, Jonathan; Bourke, Patrick; Caurvina, Nicholas; Shah, Neha Parikh; Amini, Fereshteh; Weston, Jeffrey; Park, Youngser; Vogelstein, Joshua; White, Chris; Priebe, Carey E. (Management Science, 2025)
Workplace communications around the world were drastically altered by Covid-19, work-from-home orders, and the rise of remote work. We analyze aggregated, anonymized metadata from over 360 billion emails within over 4000 organizations worldwide to examine changes in network community structures from 2019 through 2020. We find that, during 2020, organizations around the world became more siloed, evidenced by increased modularity. This shift was concurrent with decreased stability, indicating that organizational siloes had less stable membership. We provide initial insights into the implications of these network changes – which we term dynamic silos – for organizational performance and innovation.